ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Tri Roro Suprihatin; Rippi Maya; Eka Senjayawati (Jurnal Kajian Pembelajaran Matematika, 2018)
This study aims to describe students' mathematical reasoning abilities, particularly learning difficulties (Learning osbtacles) of students in understanding triangular and quadrilateral materials related to their penal ability. The subjects of the study were 34 students of class IX. This research method is qualitative descriptive by analyzing student difficulties from given instrument. Instruments in this study form a written test of mathematical reasoning ability. The result of this research shows that students' mathematical reasoning problems are good. This can be seen from the overall average of 70.